The effect of organizational identification on job embeddedness: evidence from new generation of rural migrant workers in China - Tang, MeiRun; Jennie Soo, Hooi Sin; Chuah, Chin Wei (GrowingScience.Com, 2018)
The purpose of this paper was to examine the relationships among work overload (WO), compensation (COM), organizational identification (OI) and organization embeddedness (OE) in the context of manufacturing industry in China through social identity theory. A 37-item questionnaire was filled by 384 new generation of rural migrant workers. Data were examined through a two-stage of first-order of reflective model and second-order reflective-formative hierarchical model using PLS-SEM. The empirical results indicate that COM and OI positively and significantly predicted OE, while WO was found to have no direct effect on OE. In addition, COM positively and significantly was associated with OI, whereas WO affected OI, negatively. Further examination of the mediation effects of OI revealed that OI could fully mediate the relationship between WO and OE. Moreover, OI also had a partial mediator role in the relationship between COM and OE. The study concluded with several implications and recommendations for future research.